PROFESIONALITAS APARAT PENGAWASAN FUNGSIONAL INTERN TERHADAP PELAKSANAAN AUDIT PEMERINTAHAN DAN IMPLIKASINYA KEPADA AKUNTABILITAS KEUANGAN INSTANSI PEMERINTAH DAERAH - DADANG SADELI (Jurnal Bisnis dan Akuntansi, 2008)
The research was tested empirically regarding an internal functional control-ling personnel’s professionalism effect on accomplishing the government audit as well as its implications on local government agency financial accountability. The study was conducted by survey method. The size of samples was 150 official offices and 150 team chiefs who inspected Municipal Government and Regency’s official offices in West Java Province area. The analysis method used in this research was descriptive analysis with the analysis tool using the Structural Equation Modeling. Based on the results of data analysis and discussion, it was obtained the following research findings that internal functional controlling personnel’s professionalism has positively effect on implementing government audit; implementation of government audit has implication on quality of local government agency financial accountability.